Breeding innovation clusters through collaborative research networks - Liyanage, Shantha (Technovation)
Collaborative research programs have a significant impact on the structure of national innovation systems by creating and strengthening networks which are essential for breeding innovation clusters. These networks involve both technology and market stakeholders and are extended to include industry, research and technology producers. Network activities have resulted in setting priority in research and linking research fields that have high potential to coalesce into distinct technological clusters. This paper examines the processes by which innovation clusters are formed in research collaborations by analysing the work programs of 51 Australian Cooperative Research Centres (CRCs). The paper also provides an analytical framework to determine the direction of national research setting through cluster analysis. The author employs a methodology called 'co-occurrence of words' in cluster construction. It is argued that the iterative process of innovation cluster formation is an effective form of organizing a national system of innovation. These clusters enable public policy makers to identify complementarities between generation, acquisition and diffusion of knowledge across a range of innovations rather than a single innovation.